PREVENTION AND TREATMENT OF SHEEP POISONING BY HELIOTROP PLANT (Web of Teachers: Inderscience Research, 2024)
This article was prepared on the basis of literature data the article contains information about heliotrope plant species and livestock poisoning from heliotrope.